2020
DOI: 10.17712/nsj.2020.3.20190097
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting functional outcomes of traumatic brain injury rehabilitation at a rehabilitation facility in Saudi Arabia

Abstract: Objectives: To identify the factors that affect disability after inpatient rehabilitation (IPR) in persons with traumatic brain injury (TBI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…This difference in age of the patients may be due to social norms. Our findings are similar with the results of Ullah S et al 5 in which majority of the patients with traumatic head injury were in young age group. Our study findings showed that males are mostly involved in road traffic accidents which are in agreement with results of Bhatti JA et al 6 in which most of the patients with head injury were males.…”
Section: Discussionsupporting
confidence: 93%
“…This difference in age of the patients may be due to social norms. Our findings are similar with the results of Ullah S et al 5 in which majority of the patients with traumatic head injury were in young age group. Our study findings showed that males are mostly involved in road traffic accidents which are in agreement with results of Bhatti JA et al 6 in which most of the patients with head injury were males.…”
Section: Discussionsupporting
confidence: 93%
“… 18 RTAs are the leading cause of TBI in Saudi Arabia. 6 Paralleling our local statistics, RTA was the main mechanism of injury in our report (49.7%), followed by falls (39.5%).…”
Section: Discussionsupporting
confidence: 85%
“…5 Incidence of TBI in Saudi Arabia has been estimated to be 116 per 1,00,000 population. 6 The global prevalence of TBI continues to peak in males reflecting the gender differences in social roles and behaviors. 5 TBI is one of the important causes of preventable deaths in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] A study from KSA showed that the functional outcome of patients suffering from traumatic brain injury is affected by the severity of the disability at admission and the time between injury and admission. [5] Data is limited related to the outcome of neurorehabilitation amongst patients with Prolonged Disorders of Consciousness in the UAE. This study will shed light on the effects of Neurorehabilitation on the prognosis of patients with Prolonged Disorders of Consciousness for more than two years.…”
Section: Introductionmentioning
confidence: 99%